2007
DOI: 10.1124/dmd.107.018242
|View full text |Cite
|
Sign up to set email alerts
|

Taxane's Substituents at C3′ Affect Its Regioselective Metabolism: Different in Vitro Metabolism of Cephalomannine and Paclitaxel

Abstract: ABSTRACT:To investigate how taxane's substituents at C3 affect its metabolism, we compared the metabolism of cephalomannine and paclitaxel, a pair of analogs that differ slightly at the C3 position. After cephalomannine was incubated with human liver microsomes in an NADPH-generating system, two monohydroxylated metabolites (M1 and M2) were detected by liquid chromatography/tandem mass spectrometry. C4؆ (M1) and C6␣ (M2) were proposed as the possible hydroxylation sites, and the structure of M1 was confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
(53 reference statements)
2
18
1
Order By: Relevance
“…By comparing the ratio of V max / K m , the formation of 6a-hydroxypaclitaxel was almost 9 times faster than that of p-39-hydroxypaclitaxel, suggesting that CYP2C8-mediated paclitaxel hydroxylation was more predominant in the current batch of pooled HLM. The K m and V max values observed in the present study were within 2-fold to 3-fold of the published results; this is not surprising given that laboratory-to-laboratory variability is often seen for in vitro metabolism studies (Polasek et al, 2004;Zhang et al, 2008). The differences in K m and V max values might be due to different HLM sources as well as the incubation conditions.…”
Section: Resultssupporting
confidence: 68%
“…By comparing the ratio of V max / K m , the formation of 6a-hydroxypaclitaxel was almost 9 times faster than that of p-39-hydroxypaclitaxel, suggesting that CYP2C8-mediated paclitaxel hydroxylation was more predominant in the current batch of pooled HLM. The K m and V max values observed in the present study were within 2-fold to 3-fold of the published results; this is not surprising given that laboratory-to-laboratory variability is often seen for in vitro metabolism studies (Polasek et al, 2004;Zhang et al, 2008). The differences in K m and V max values might be due to different HLM sources as well as the incubation conditions.…”
Section: Resultssupporting
confidence: 68%
“…Meanwhile, CYP3A4 instead of CYP2C8 becomes the primary monooxygenase. The present authors' recent study on the metabolic profile of cephalomannine (Figure 1, V) also suggested that relatively minor modification of the taxane molecule at C-3′ has a major consequence on the regioselective metabolism mediated by CYP3A4 (Zhang et al 2008a). Furthermore, the presence of an acetyl group at C-10 of the taxane ring strikingly activates hydroxylation by both CYP2C8 and CYP3A4 (Cresteil et al 2002).…”
Section: Introductionmentioning
confidence: 77%
“…The eluent was monitored at 227 nm with a flow rate of 1 ml min −1 . Commercial standards for the unknown metabolites of 7-epi-cephalomannine and 7-epi-10-deacetyl-paclitaxel were not available, and all detected metabolites contained the taxane ring as a chromophore (Gut et al 2006); therefore, 7-epi-cephalomannine and 7-epi-10-deacetyl-paclitaxel were used as standards, assuming an identical molar extinction coefficient, as described previously (Vaclavikova et al 2004;Zhang et al 2008a).…”
Section: Lc/ms Methodsmentioning
confidence: 99%
“…It is interesting to note that when both phenyl and benzamide at C3Ј of C13 side chain were replaced by N-␣-tert-butyloxycarbonyl amino group and an alkyl or alkenyl group, respectively, the major hydroxylation site was again moved from tert-butyl to the alkyl group (Frapolli et al, 2006;Gut et al, 2006). Zhang et al (2008) investigated how different substitutes at the C3Ј position of taxane analogs affected its metabolism with cephalomannine and paclitaxel, a pair of analogs that differ slightly at the C3Ј position. Their results showed that relatively minor modification of taxane at C3Ј has a major consequence on the metabolism.…”
Section: Discussionmentioning
confidence: 99%